Integration of SEM to VIKOR for Benchmarking Repurchase Intentions in Gated Communities - Faraj, Khayal Mahsum; Sahin, Osman; Ibrahim, Zrian Ibrahim (International Journal of Psychosocial Rehabilitation, 2020)
Aim of this study is to benchmark the repurchase intentions of residents in gated communities in Kurdistan Region of Iraq. to do this, we have collected data from the 320 residents of various gated communities. Secondly, we have used SEM and VIKOR multi methodology to propose benchmarking. The results have indicated the impact of each criterion on the repurchase intention while using those impact as importance weights to rank gated communities in the region. Lastly, the study contains managerial implications explained in the conclusion part.